URGENSI PENGUATAN REGULASI PELINDUNGAN DATA DAN KEAMANAN SIBER DI INDONESIA TERHADAP ANCAMAN HACKING DALAM SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK - Darmawan, Christhoper Kristian; Sebastian, Ezra; Notokusumo, Frederick Leroy; Loprang, Jeshua Resa (Jurnal Suara Keadilan, 2025)
The rapid advancement of information technology has introduced new challenges in cybercrime enforcement. The Bjorka case, involving data breaches and leaks of state secrets, highlights the weaknesses in Indonesia’s cyber regulations. This study aims to analyze the limitations and effectiveness of Indonesia’s Electronic Information and Transactions Law (UU ITE) and Personal Data Protection Law (UU PDP) in addressing cybercrime, comparing them with the cyber law framework in the United States. This research employs a normative juridical approach with a comparative analysis of both legal systems. The findings reveal that UU ITE lacks specific provisions on transnational cybercrime, cross-border jurisdiction mechanisms, and critical information infrastructure protection. In contrast, the United States has a more comprehensive legal framework, such as the Computer Fraud and Abuse Act (CFAA) and the CLOUD Act, which provide broader enforcement authority in handling similar cases. This study recommends the establishment of more specific cybercrime regulations, strengthening international cooperation, and enhancing law enforcement capabilities in cyber investigations. By implementing a more adaptive legal framework, Indonesia can effectively mitigate the growing threats of cybercrime thru Indonesia Cyber security and resilience law (RUU KKS)